Litchi flower essential oil balanced lipid metabolism through the regulation of DAF-2/IIS, MDT-15/SBP-1, and MDT-15/NHR-49 pathway - Chen, Yun; Qin, Qiao; Luo, Jingrui; Dong, Yusi; Lin, Chunxiu; Chen, Houbin; Cao, Yong; Chen, Yunjiao; Su, Zuanxian (Frontiers in Nutrition, 2022)
Many litchi flowers are discarded in China every year. The litchi flower is rich in volatile compounds and exhibits strong anti-obesity activity. Litchi flower essential oil (LFEO) was extracted by the continuous phase transformation device (CPTD) independently developed by our research group to recycle the precious material resources in litchi flowers. However, its fat-reducing effect and mechanism remain unclear. Employing Caenorhabditis elegans as a model, we found that LFEO significantly reduced fat storage and triglyceride (TG) content in normal, glucose-feeding, and high-fat conditions. LFEO significantly reduced body width in worms and significantly decreased both the size and number of lipid droplets in ZXW618. LFEO treatment did not affect energy intake but increased energy consumption by enhancing the average speed of worms. Further, LFEO might balance the fat metabolism in worms by regulating the DAF-2/IIS, sbp-1/mdt-15, and nhr-49/mdt-15 pathways. Moreover, LFEO might inhibit the expression of the acs-2 gene through nhr-49 and reduce β-oxidation activity. Our study presents new insights into the role of LFEO in alleviating fat accumulation and provides references for the large-scale production of LFEO to promote the development of the litchi circular economy.